Fully automated targeted confocal and single-molecule localization microscopy - Eberle, Jan Philipp; Muranyi, Walter; Erfle, Holger; Gunkel, Manuel (Super-resolution microscopy, 2017)
Single-molecule localization microscopy (SMLM) enables imaging of biological structures in the nanometre range. Long measurement times are the consequence of this kind of microscopy due to the need of acquiring thousands of images. We built a setup that automatically detects target structures using confocal microscopy and images them with SMLM. Utilizing the Konstanz Information Miner (KNIME), we were able to connect a confocal microscope with an SMLM unit for targeted screening. In this process, we developed KNIME plugins to communicate with the microscope components and combined them to a workflow. Thus, measuring biological nanometre-sized structures in a sufficient number to get statistical significance becomes feasible. For proof of principle HIV-1 assembly complexes in HeLa cells derived from transfection of replication deficient viral construct were imaged by a fully automated screen.